Use of low power laser in the treatment of oral injuries in patients with neurological diseases: Case report (Research, Society and Development, 2021)
The therapy of Photobiomodulation with Low Power Laser has been used in the prevention and handling of oral injuries. Objective: to report a case on the treatment of traumatic oral injury with photobiomodulation therapy. Methodology: Based on the permission through the Free and Informed Consent Term (ICF) to share the images for due purpose, the present study deals with a case report of a descriptive analytical nature. Case report:  A 43-year-old male patient from a hospital in São Luís was diagnosticated with a new ischemic stroke. Over the hospitalization after dependence on mechanical ventilation, the patient developed from an orotracheal tube to a tracheostomy, exponent autophagy of the lower lip as a consequence foul of muscular coordination and potentialized movements during manipulation. On physical odontological exam, the teeth 11 and 12 were, with huge injury on lower lip; using the Guedel cannula and where Triamcinolone Acetonide was prescribe as therapy. After the dental appreciation, the treatment plan consisted in removing instantly the cannula, optimization of analgesia, fabrication of occlusal plaque, wear of incisal faces of teeth 11 and 12, hanging of Triamcinolone,clean the area and application of low-power laser with the wavelength 660 nm, 100 mW of power, time of  20 seconds, 2J of energy, in 3 sessions. Result: Was observed in 24 hours after the laser application the injury regression. were maintained the use of plaque and follow-up after discharge from the ICU. Conclusion: The use of the photobiomodulation therapy proved to be an effective tool in the healing of traumatic oral injuries.